Russia's first modern Jews : the Jews of Shklov - Fishman, David E., 1957- (Reappraisals in Jewish social and intellectual history., 1995)
Long before there were Jewish communities in the land of the tsars, Jews inhabited a region which they called medinat rusiya, the land of Russia. Prior to its annexation by Russia, the land of Russia was not a center of rabbinic culture. But in 1772, with its annexation by Tsarist Russia, this remote region was severed from the Polish-Lithuanian Commonwealth; its 65,000 Jews were thus cut off from the heartland of Jewish life in Eastern Europe. Forced into independence, these Jews set about forging a community with its own religious leadership and institutions. The three great intellectu.